A Systematic Literature Review (SLR) on the Development of Sustainable Heritage Cities in Malaysia - Yazid Saleh; Hanifah Mahat; Mohmadisa Hashim; Nasir Nayan; Samsudin Suhaily; Mohamad Khairul Anuar Ghazali; Rahma Hayati; Rahma Kurnia Sri Utami (The Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
This article highlights previous studies on the development of sustainable heritage cities using the Systematic Literature Review (SLR) method. Data obtained through various search methods, such as (1) a rigorous search of leading major journal databases (Scopus, Web of Science (WOS), Science Direct) and additional journal databases (Google Scholar and My Cite), and (2) handpicking/manual searching. Once the data was obtained, it was analysed through systematic searching strategies (SSS) to obtain accurate and precise material in the field studied. The obtained material was screened in three SSS steps, namely: (1) identification (2) screening, and (3) eligibility. As a result, a total of 42 materials and documents were successfully found and summarized for highlighting. Next, the findings of the analysis were broken down into: (1) the frequency of sustainable urban heritage development studies conducted by country, (2) sustainable urban heritage development constructs (economic prosperity, social well-being, environmental well-being, cultural heritage, government, and community), and (3) study areas (heritage cities, heritage buildings, and historical sites). The findings of this study can contribute to a new paradigm for studies that involve the sustainable development of heritage cities in Malaysia in achieving the 2030 Agenda. Abstrak. Artikel ini menyoroti studi sebelumnya terkait pengembangan kota warisan berkelanjutan menggunakan metode Systematic Literature Review (SLR). Data diperoleh melalui berbagai metode pencarian, seperti (1) pencarian dari basis data jurnal terkemuka (Scopus, Web of Science (WOS), Science Direct) dan basis data jurnal tambahan (Google Scholar dan My Cite), dan (2) pencarian manual. Setelah itu, dilakukan analisis melalui strategi pencarian sistematis (SSS) untuk mendapatkan materi yang akurat dan tepat pada keilmuan yang diteliti. Materi yang diperoleh disaring dalam tiga langkah SSS, yaitu: (1) identifikasi, (2) penyaringan, dan (3) tingkat kelayakan. Hasilnya, terdapat total 42 materi dan dokumen yang berhasil ditemukan dan dirangkum untuk disorot. Selanjutnya, temuan analisis dibagi menjadi: (1) frekuensi studi pengembangan warisan kota berkelanjutan yang dilakukan oleh negara, (2) konstruksi pengembangan warisan kota berkelanjutan (kemakmuran ekonomi, kesejahteraan sosial, kesejahteraan lingkungan, budaya cagar budaya, pemerintah, dan masyarakat), dan (3) kawasan studi (kota cagar budaya, bangunan cagar budaya, dan situs sejarah). Temuan penelitian ini dapat berkontribusi pada paradigma baru untuk studi yang melibatkan pembangunan berkelanjutan kota warisan di Malaysia dalam mencapai Agenda 2030. Kata kunci. Pembangunan berkelanjutan, kota warisan, Systematic Literature Review (SLR), Malaysia.